Fundamental statistical methods for analysis of Alzheimer's and other neurodegenerative diseases - Irimata, Katherine E., 1990- (Johns Hopkins University Press, 2020)
"This book explains statistical techniques commonly used in analyzing data for Alzheimer's and other neurodegenerative diseases, and it presents examples from real-world applications in an effort to make the techniques useful for professionals and students. The book leads readers through the steps of conducting multivariate analyses while adjusting for correlation or the hierarchical structure of data in prediction and inferences. Techniques such as spatial analysis, Bayesian analysis, and time-dependent covariates are included. Several data sets from the National Alzheimer's Coordinating Center are analyzed with statistical software commonly used by Alzheimer's researchers, and the results are shown to readers by way of illustration"--